PERENCANAAN PENJADWALAN DISTRIBUSI PRODUK SEPATU PANTOFEL DENGAN MENGGUNAKAN METODE DISTRIBUTION REQUIREMENT PLANNING (DRP) DI HOME INDUSTRI THREE STAR’S - Hidayat, Rocmat; Munir, Misbah (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2018)
Customer satisfaction is very influential in the business world, where customers always need a cheap and quality products and timely delivery, A company will be faced with a problem associated with the product distribution system arising because consumers are in a geographically dispersed location or area, so the delivery Goods not in accordance with the time specified. Distribution Requiremnt Planning Is a method for dealing with supply procurement of a multi echelon distribution network. DRP method is expected to help the problem of scheduling distributed activities, so that the success in fulfilling customer demand will be more optimal, sales performance will increase in order to meet the order with timely and exact amount so that the cost of distribution can be reduced to a minimum. Results obtained Planning Distribution Research company method, the Total Cost of distribution data meliputu product demand, product price, booking fees, storage fees, shipping costs, lead time data with DRP method is smaller when compared with the methods of the company. Total Cost (TC) with the method the company is at Rp.33.865.440,- and total Cost with method is Rp. 23.380.224. So there is the difference between the total Cost companies a total cost of 69% method.